Effects of Melatonin on Neurological Function and Maintenance of Physical and Motor Fitness in Collegiate Student-Athletes Following Sleep Deprivation - Paryab, Nesa; Taheri, Morteza; Irandoust, Kahdijeh; Mirmoezzi, Masoud (International journal of sport studies for health, 2020)
Background: Melatonin is one of the Supplements used to treat sleep problems such as insomnia and jet lag. Objectives: Since sleep deprivation may affect athletic performance, the aim of this study was to investigate the effect of melatonin on neurological function and maintenance of physical and motor fitness in collegiate student-athletes following sleep deprivation. Methods: Ten collegiate student-athletes participated in randomized, double‐blind crossover trial with placebo control. Subjects were divided into six experimental groups: without sleep deprivation (WSD), 4 hours sleep deprivation (4HSD) and 24 hours sleep deprivation (24HSD) with melatonin (MEL) or placebo (PLA). WSD were allowed to sleep eight hours per night. Six milligrams of melatonin was administered 30 min before the training protocols. Training protocols included the Wingate Anaerobic test, Good Balance test, Vienna reaction time with the Stroop test. Data were analyzed using repeated measures ANOVA. Significant difference was set at P ≤ 0.05. Results: Six mg/day of MEL 30 min before training had no significant effect on anaerobic power, balance and reaction time in collegiate student-athletes WSD (P > 0.05). Although, 4HSD and 24HSD negatively affected balance function, MEL reduced its negative effects. Furthermore, 24HSD decrease neurological and physical performance in collegiate student-athletes and MEL improved anaerobic power and reaction time in collegiate student-athletes (P < 0.05). Conclusions: Pre-training MEL supplementation would alleviate neurological, physical and motor performance impairment in collegiate student-athletes following sleep deprivation. MEL appears to be more effective in athletes with longer sleep deprivation.